2010
DOI: 10.1111/j.1574-6941.2010.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification exhibits Haldane kinetics in an agricultural soil treated with ammonium sulfate or dairy-waste compost

Abstract: An agricultural soil was treated with dairy-waste compost, ammonium-sulfate fertilizer or no added nitrogen (control) and planted to silage corn for 6 years. The kinetics of nitrification were determined in laboratory-shaken slurry assays with a range of substrate concentrations (0-20 mM NH(4)(+)) over a 24-h period for soils from the three treatments. Determined concentrations of substrate and product were fit to Michaelis-Menten and Haldane models. For all the treatments, the Haldane model was a better fit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 28 publications
2
43
1
Order By: Relevance
“…A subsequent study has shown that the factors controling the relative contributions are complex with cropping treatment, soil conditions, and NH 4 + availability influencing their relative contributions in the field (Taylor et al, 2012). Using soils from our same site, investigations into the kinetics of ammonia oxidation found K m values similar to other soils (0.02 mM) but less than for pure cultures of AOB (Koper et al, 2010). Based on the above mentioned studies, AOB will likely be relatively more important players in the AS and LW treated plots in our system, with AOA being functionally more important in the control and DC treated plots.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…A subsequent study has shown that the factors controling the relative contributions are complex with cropping treatment, soil conditions, and NH 4 + availability influencing their relative contributions in the field (Taylor et al, 2012). Using soils from our same site, investigations into the kinetics of ammonia oxidation found K m values similar to other soils (0.02 mM) but less than for pure cultures of AOB (Koper et al, 2010). Based on the above mentioned studies, AOB will likely be relatively more important players in the AS and LW treated plots in our system, with AOA being functionally more important in the control and DC treated plots.…”
Section: Resultsmentioning
confidence: 64%
“…The spring fertilizer pulse of available ammonium will most likely stimulate activity and possibly growth of AOB over a short period of time (Shi et al, 2004). In these soils nitrification rates are rapidly increased by ammonium additions when compared to gross nitrification rates suggesting ammonium limitation of ammonia oxidation (Habteselassie et al, 2006b; Koper et al, 2010). In a soil microcosm study, Okano et al (2004) reported 8 and 11 fold increases in AOB population size one week after AS applications at 80 and 400 kg N ha -1 rates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This method originated from the work of Belser and Mays (1980) and is common practice for evaluating the activity of ammonia monooxygenase (AMO) (e.g., Ö quist et al 2004; Koper et al 2010;Prosser and Nicol 2012). AOP was measured on August 18, 2009, i.e., 9 days after the sampling.…”
Section: Measurement Of Aopmentioning
confidence: 99%
“…Zhang et al (2009) 66-17.69%, 6.41-11.72%, and 7.42-13.35% in 2010, 2011, and 2012, respectively (Table 6), significantly lower than the percentages represented by NO 3 − -N. These results were observed primarily because NH 4 + -N is easily adsorbed by both soil particles and soil organic matter (Ardakani et al, 1974;Rosenfeld, 1979). Under aerobic conditions, NH 4 + -N can be quickly converted into NO 3 − -N through nitrification and can also be lost through ammonia volatilization (Koper et al, 2010;Salazar et al, 2012). The results also indicated that as rainfall increased, the percentage of TN runoff losses represented by NO 3 − -N runoff losses decreased, whereas that represented by NH 4 + -N increased.…”
Section: Characteristics Of N Runoff Losses From Vegetable Fieldsmentioning
confidence: 92%